Xét A=a33a−ab−ca+2bc:=a3a2+ab+ac−ab−ac+2bc=a3a2+2bc=a2.a+2abc−2abca2+2bc =a−2abca2+2bcNên, S=a+b+c−2abc(1a2+2bc+1b2+2ca+1c2+2ab)+3abc $\leqslant - 2abc (\frac{9}{(a+b+c)^2}) +3abc\leqslant 3 - 2abc + 3abc = 3 + abc\leqslant 3 + \frac{(a+b+c)^3}{27}= 3+1 = 4Dấu=xảyra\Leftrightarrowa=b=c=1$
Xét
A=a33a−ab−ca+2bc:
=a3a2+ab+ac−ab−ac+2bc=a3a2+2bc=a2.a+2abc−2abca2+2bc =a−2abca2+2bcNên,
S=a+b+c−2abc(1a2+2bc+1b2+2ca+1c2+2ab)+3abc $\leqslant
3- 2abc (\frac{9}{(a+b+c)^2}) +3abc
\leqslant 3 - 2abc + 3abc
= 3 + abc
\leqslant 3 + \frac{(a+b+c)^3}{27}
= 3+1 = 4
Dấu=
xảyra\Leftrightarrow
a=b=c=1$